A study on the development of a fishing shipyard in Peukan Bada District, Aceh Besar using fishbone analysis: A short comunnication - Thaib Rizwan; Durratul Hikmah; Muhammad Muhammad; Makwiyah A. Chaliluddin; Akhyar Akhyar; Razali Thaib (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
The People of Peukan Bada generally work as fishermen. The ships used by the Peukan Bada people are generally wooden material. The capture fisheries sector in the Peukan Bada area is currently still small in scale. This can be seen from the type of fishing gear used by ships operating in the waters of Peukan Bada. The problem is that the shipbuilding industry in Peukan Bada is currently not developing following the challenges faced. So it is necessary to develop a fishing boat yard in the area. The purpose of this research is to find out what meters need to be considered in the development process. The method of collecting data used in this study is the survey method. The survey that will be carried out is by directly observing the conditions and assessing factors related to fishing vessels, the data needed to support this research method is primary data. The primary data were obtained from direct observations of various activities carried out in the shipyard and the results of interviews obtained with workers in the shipyard. The data analysis used is Fishing Bone Analysis the result of this research is that this shipbuilding industry has developments that are still far from capacity, potential, needs, and the need for the development of land parameters, human resources, machinery, materials, methods or ways of working, shipping flows and production capacity.